Development of Linktree-Based Interactive Learning Media to Improve History Learning Outcomes - Fadliati Harna; Abdul Muin Sibuea; Samsidar Tanjung (Randwick International of Education and Linguistics Science Journal, 2024)
The aim of this research is to produce Linktree learning media products aimed at testing aspects of the feasibility, practicality, and effectiveness of Linktree-based interactive learning media to improve history learning outcomes in class XI MAN 2 Medan Model. The research and development method used is the ADDIE model. The research results show: (1) The material expert validation test is very feasible with 93.75%. (2) The validation test for media experts is very feasible at 95%. (3) validation test of learning design experts in the very feasible category with 100%. (4) Individual trials in very feasible criteria with 83.92%. (5) The small group trial criteria were very feasible, with 89.83%. (6) Field trials met very feasible criteria with 94.06%, with an overall average result of 93.02%. Then the results of the experiment using Linktree-based interactive learning media using the problem-based learning model approach in the experimental class had an average learning outcome of 89.9, while using Linktree-based interactive learning media with the cooperative learning jigsaw model approach in the control class had an average value of 83.8. Based on the independent T-test, the effectiveness test showed a Sig value. (2-tailed) 0.000 is <0.05, which means it is significant. It was concluded that the Linktree-based interactive learning media with the problem-based learning model approach was effectively used to improve history learning outcomes. Based on the N-Gain calculation, a result of 60.96 was obtained in the quite effective category.